The stronger than BPD journal : DBT activities to help women manage emotions and heal from borderline personality disorder - Corso, Debbie; Holt, Kathryn C. (New Harbinger Publications, Inc., 2018)
"Your story is just beginning. In The Stronger than BPD Journal, influential BPD blogger, advocate, and peer educator Debbie Corso and psychotherapist Kathryn C. Holt offer guided writing activities to help you work through strong emotions, strengthen emotional resiliency, and build lasting relationships. If you have borderline personality disorder (BPD), you may have trouble managing your intense emotions, navigating day-to-day life, and maintaining healthy relationships. You may also have trouble seeing yourself clearly beyond your diagnosis. But you should know that--while BPD is a part of your life's story--BPD isn't the whole story. This unique journal offers gentle guided exercises based in dialectical behavior therapy (DBT) to help you balance your emotions, take time for self-care and exploration, and put a stop to overly critical self-judgment. You'll also learn to reduce stress, upsets, and triggers; gain resiliency; and improve communication with others. Writing can be a vehicle for profound self-reflection, exploration, and healing. This guided journal will help you take control of your emotions, gain insight into your unique mind, and start living the life you deserve"--